2022
DOI: 10.1016/j.arthro.2021.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Greater Psychological Readiness to Return to Sport, as Well as Greater Present and Future Knee-Related Self-Efficacy, Can Increase the Risk for an Anterior Cruciate Ligament Re-Rupture: A Matched Cohort Study

Abstract: Greater psychological readiness to return to sport, as well as greater present and future knee-related self-efficacy can increase the risk for an ACL re-rupture: a matched cohort study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
1
31
0
3
Order By: Relevance
“…the strongest association with the outcome, whereas ACL-RSI was not selected with the longer follow-up times. Previous studies have shown an association with ACL-RSI and second ACL injury in follow-up periods of approximately 2 years after ACLR [ 37 , 38 ], indicating that psychological readiness for RTS may be more important in the short-term follow-up. This confirms the hypothesis that the association between psychological readiness and injury will decrease with longer follow-up times.…”
Section: Discussionmentioning
confidence: 99%
“…the strongest association with the outcome, whereas ACL-RSI was not selected with the longer follow-up times. Previous studies have shown an association with ACL-RSI and second ACL injury in follow-up periods of approximately 2 years after ACLR [ 37 , 38 ], indicating that psychological readiness for RTS may be more important in the short-term follow-up. This confirms the hypothesis that the association between psychological readiness and injury will decrease with longer follow-up times.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the incorporation of data from non-operatively treated ACL-injured patients, rehabilitation-specific registries assessing psychometric PROMs, measures of risk appraisal, and muscle function [ 52 , 53 ] will open new avenues for the evaluation of ACL injury treatment outcomes. Merger of data from registries with different aims will provide a more complete picture of the operative and postoperative course of ACL-R patients and permit more complex analyses of outcomes following ACL surgery.…”
Section: Methods Used In Registry Studiesmentioning
confidence: 99%
“…25 Secondly, with regard to PROs, both a relatively negative psychological response (60.8 on the ACL-Return to Sport after Injury (ACL-RSI)) scale and a positive (81.2 on the ACL-RSI) psychological response have been associated with a risk of a second ACL injury. 26,27 Finally, Beischer et al 28 found that patients who RTS < 9 months after ACL reconstruction run a seven times higher risk of suffering a second ACL injury compared with patients who RTS > 9 months after ACL reconstruction, but the results are not always reproduced. 29 As inferior postoperative outcomes have been found in patients with GJH following ACL reconstruction when compared with patients without GJH, 14,15 the presence of GJH might also in uence RTS after ACL reconstruction.…”
Section: Yes/nomentioning
confidence: 99%